The little mermaid - Ellis; Louise (Thaxted Miles Kelly, 2016)
PICTURE STORYBOOKS. Princess Time The Little Mermaid is a beautiful picture book for children aged 3+. Every page of this beautiful picture book showcases full-bled artwork, packed with charm and detail. Louise Ellis, a talented children's artist, has delightfully illustrated the timeless tale, which has been simply and thoughtfully retold to appeal to young readers and listeners alike. Ages 0+